Vasilyev about Crimean Gothia of the Second Half of the 10th – the Beginning of the 11th Century - Valeriy P. Stepanenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
Introduction. In the national historiography there is an opinion that the work of A.A. Vasilyev The Goths in the Crimea still remains the most authoritative, if not the only research on this problem. However, the reference to the sources used by him gives grounds to assume that a certain part of the facts given by him is not based on the data of these sources, being a consequence of the logical constructions of the researcher. As a result, the author’s methodology as well as his conclusions need a more critical approach.